2020
DOI: 10.1097/aog.0000000000003750
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Tranexamic Acid in Postpartum Women After Oral Administration

Abstract: Personal or nonessential information may be redacted at the editor's discretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Importantly, our modified plasmin activity halo assay, which looks at plasmin activity in the presence of an established fibrin clot, confirmed that the plasma level of TXA had effectively inhibited fibrinolytic activity. Previous pharmacokinetic studies of TXA in human plasma after oral administration (2 g) reported that plasma TXA levels reached ∼10 μg/mL [ 51 ], and consistent with this, other studies have suggested that the most effective level of TXA to block fibrinolysis is within the 10- to 15-μg/mL range [ 52 ]. These levels are ∼20 times more than the level we report in mouse plasma; however, the administration regime is markedly different: while the human data are derived from a bolus 2-gram TXA tablet, in our study, TXA (20 mg/mL) was added to the drinking water for the duration of the entire 6-month study.…”
Section: Discussionsupporting
confidence: 61%
“…Importantly, our modified plasmin activity halo assay, which looks at plasmin activity in the presence of an established fibrin clot, confirmed that the plasma level of TXA had effectively inhibited fibrinolytic activity. Previous pharmacokinetic studies of TXA in human plasma after oral administration (2 g) reported that plasma TXA levels reached ∼10 μg/mL [ 51 ], and consistent with this, other studies have suggested that the most effective level of TXA to block fibrinolysis is within the 10- to 15-μg/mL range [ 52 ]. These levels are ∼20 times more than the level we report in mouse plasma; however, the administration regime is markedly different: while the human data are derived from a bolus 2-gram TXA tablet, in our study, TXA (20 mg/mL) was added to the drinking water for the duration of the entire 6-month study.…”
Section: Discussionsupporting
confidence: 61%
“…administration of TXA also leads to plasma concentrations considered effective. 24 , 25 , 26 Although measuring TXA concentration is feasible in scientific studies, it is not possible in clinical practice, as laboratory coagulation tests and conventional viscoelastic measurements can only indirectly depict fibrinolysis. tPA-modified ROTEM 27 and plasmin-spiked TEG assays 28 have been described; however, the ClotPro TPA-test is the first commercially available viscoelastic assay to directly visualise inhibition of fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The mean time to maximum plasma concentration was 2.9 h (range 2.5–3.5 h). Mean time taken to reach the plasma concentration of 5 mg/L was 0.9 h 28 . Although levels reached were within range to partially inhibit fibrinolysis, the time taken to reach these levels would lead to significant delay when treating PPH with TXA because with every 15 min of treatment delay the benefit of TXA decreases by about 10%, with no benefit after 3 h 18 …”
Section: Alternative Routes To IV Txa and Their Effectivenessmentioning
confidence: 99%